Novel method for building ancient recombination landscape using archaic human genomes - Tumian, Afidalina (2020)
PRDM9 is a human zinc finger (ZF) gene responsible for initiating much or all of human recombination. PRDM9 shows extreme variation in both number and sequence of its ZFs, between species and amongst individuals, across mammals. The commonest PRDM9 allele binds the human hotspot motif, CCNCCNTNNCCNC, but other human alleles bind different targets. The rapid evolution of the PRDM9 ZF array may be a response to escape selfdestructive drive called biased gene conversion (BGC).